Dampak Media Sosial akan Gaya Hidup Mahasiswa Universitas Tulungagung - Nabila, Dian Ayu; Masitoh, Umi; Aprillianti, Veni (FISIP UWP, 2023)
Social media makes it easier for users to communicate with each other or share content in the form of photos, videos, text or sound just by using a monitor screen. Social media users in Indonesia have reached 210 million users, with the biggest users being young people or students. The use of the internet is not only as a medium of communication but can be used in the industrial sector, education, business, etc. It is undeniable that the development of the internet is very influential in changing human lifestyles. This study aims to determine and describe the impact of social media on the lifestyle of Tulungagung University students. The research method that researchers use is a type of qualitative descriptive research. The results of the study show that social media is media that allows its users to participate in social activities through the internet which is not limited by distance, space or time. Tulungagung University students use social media such as WhatsApp, Instagram, Tiktok and Facebook. Social media has become a necessity and even a lifestyle for Tulungagung University students